Study on epitope mapping of hemagglutinin protein in h5n1 influenza virus - Chahal, Anterpreet Kaur (My University, 2013)
Influenza viruses circulating in animals pose threats to human health. Humans can be infected with influenza viruses from animal sources, such as pigs and birds. H5N1 also called bird flu is one of recent strain of influenza which causes death in birds as well as in human. Although human to human transmission of this disease is not clearly reported. The primary risk factor for human infection appears to be direct or indirect exposure to infected live or dead animals or contaminated environments. Current influenza virus vaccines protect mostly against one particular strain. Hence great challenge in the field of influenza virus research is to design a universal vaccine. In our study we have considered the conserved peptide of hemagglutinin protein (HA) of H5N1 Virus to predict the epitope. Nine conserved peptide sequences from 163 HA protein sequences were obtained. Thirty and eleven epitopes were predicted for MHC Class I T and B cell respectively based on immuninformatics approach. Seven and two immunogenic peptides were generated by considering the overlapping epitopes MHC Class I T and B cell respectively. These immunogenic peptides can be validated for their immunogenic response in the in-vitro system which can be an interesting candidate for vaccine design against the H5N1 influenza virus vaccine.
Master of Science-Microbiology
Keywords: epitope; influenza